KESULITAN BELAJAR IPS PADA SISWA SEKOLAH DASAR PADA KURIKULUM MERDEKA : STUDI PADA SD NEGERI TUKANGAN YOGYAKARTA - Dewi Tien Utami; Dhiniaty Gularso (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research describes the social studies learning difficulties of class V students at SD Negeri Tukangan Yogyakarta. This research uses qualitative methods with data collection methods, namely observation, interviews and documentation with the research subjects as fifth grade students at SD Negeri Tukangan Yogyakarta, with a total of 22 students. The data analysis technique uses qualitative descriptive analysis, the Miles & Huberman model includes data collection, reduction, presentation and drawing conclusions. The results of the research show that students experience difficulties in the rich Indonesian material, especially the sub-material of Indonesia's geographical and astronomical location as well as national cultural wisdom. Forms of student learning difficulties include difficulty understanding the subject matter. Limited learning resources, lack of interest in social studies lessons, and the implementation of learning that is still not going well are factors causing students' lack of understanding of social studies material.